EMPIRICAL RESEARCH IN CONTEXT OF LAW - Abdul Ghaffar Korai; Imtiaz Ahmed Memon; Ahad Ghaffar; Abdul Samad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This Empirical Law study (ELS) examines research questions in law to study the operation and function of law, as well as its influence, using social science research methods. The growing trend of putting hypotheses and questions to the test has been dubbed the "next big thing" in legal science, even a revolution whose significance has been overlooked thus far. Qualitative method was used for this study. It was concluded that legalising abortion causes an increase in criminal behaviour.The results of this study lend credence to the following claim; All countries that had legalised abortion previously saw significant reductions in criminal activity. The inverse relationship between abortion rates and crime rates also applies in states with lower abortion rates.